Numerical investigation of the effect of boundary conditions on hydroelastic stability of two parallel plates interacting with a layer of ideal flowing fluid - Bochkarev, Sergey Arkadievich; Lekomtsev, Sergey Vladimirovich (Computational Continuum Mechanics, 2015)
The paper studies the hydroelastic stability of two parallel identical rectangular plates interacting with a flowing fluid confined between them. General equations describing the behavior of ideal compressible liquid in the case of small perturbations are written in terms of the perturbation velocity potential and transformed using the Bubnov-Galerkin method. The small deformations of elastic plates are defined using the first-order shear deformation plate theory. A mathematical formulation of the dynamic problem for elastic structures is developed using the variational principle of virtual displacements, which takes into account the work done by the inertial forces and hydrodynamic pressure. The numerical solution of the problem is carried out in three-dimensional formulation by means of the finite element method. A stability criterion is based on the analysis of complex eigenvalues of the coupled system of equations obtained for different values of flow velocity. The existence of different types of instability has been shown depending on the combinations of the kinematic boundary conditions defined at the edges of both plates. We considered both the symmetric and asymmetric types of clamping. It has been found that the dependence of the lowest eigenfrequency of two parallel plates on the height of quiescent fluid is nonmonotonic with a pronounced peak. At the same time, critical velocities for instability change insignificantly if the distance between plates is greater than half of the maximum linear dimensions of the structure. It should be noted that the critical velocities of divergence increase monotonically with growth of the height of the fluid layer, but critical velocities for the onset of flutter instability have sharp jumps. The cause of these jumps is a change in the mode shapes at which the system loses stability.